2010
DOI: 10.1111/j.1600-6143.2009.02924.x
|View full text |Cite
|
Sign up to set email alerts
|

Anti-thrombin Therapy During Warm Ischemia and Cold Preservation Prevents Chronic Kidney Graft Fibrosis in a DCD Model

Abstract: †Authors contributed equally to this paper. Ischemia reperfusion injury (IRI) is pivotal for renal fibrosis development via peritubular capillaries injury.Coagulation represents a key mechanism involved in this process. Melagatran R (M), a thrombin inhibitor, was evaluated in an autotransplanted kidney model, using Large White pigs. To mimic deceased after cardiac death donor conditions, kidneys underwent warm ischemia (WI) for 60 min before cold preservation for 24 h in University of Wisconsin solution. Treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
61
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(64 citation statements)
references
References 48 publications
(51 reference statements)
1
61
0
2
Order By: Relevance
“…1,4,5 As a result, the Smads induce fibroblasts to differentiate into myofibroblasts. 7,8 Unilateral ureteral obstruction (UUO) is a well-established experimental model for the study of the mechanisms behind renal interstitial fibrosis (IF) and for evaluating potential therapeutic approaches that might ameliorate the fibrosis. 9,10 Although most patients with CKD are diagnosed well before they reach end-stage renal failure, effective treatments that can completely halt the progressive decline in renal functions have not yet been developed.…”
Section: Introductionmentioning
confidence: 99%
“…1,4,5 As a result, the Smads induce fibroblasts to differentiate into myofibroblasts. 7,8 Unilateral ureteral obstruction (UUO) is a well-established experimental model for the study of the mechanisms behind renal interstitial fibrosis (IF) and for evaluating potential therapeutic approaches that might ameliorate the fibrosis. 9,10 Although most patients with CKD are diagnosed well before they reach end-stage renal failure, effective treatments that can completely halt the progressive decline in renal functions have not yet been developed.…”
Section: Introductionmentioning
confidence: 99%
“…The sterile inflammation induced by ischemia-reperfusion is linked to coagulation through the activation of tissue factor, thrombin production, fibrin deposition and the activation of the protease-activated receptors [72]. Using our pediatric porcine preclinical model of kidney transplantation, we observed that a direct inhibitor of thrombin prevented delayed graft function [73]. Due to their close contact with blood flow, endothelial cells are an easy-to-reach therapeutic target during organ preservation.…”
Section: Strategies To Limit Renal Ischemia-reperfusion Injuries and mentioning
confidence: 99%
“…This suggested that PEG associated to an intracellular solution improved oxidative metabolism and reduced renal medulla injury, also in a concentration-dependent manner. Furthermore, the addition of antioxidative (Baumert et al, 1999) or anticoagulant (Favreau et al, 2010) molecules, trimetazidine and melagatran respectively, into the preservation solution increased the performance of the hypothermic conservation. The effect of trimetazidine during conservation with EC or UW showed interesting results.…”
Section: In Vivo Autotransplantation Pig Modelmentioning
confidence: 99%